Dental implants coated with a durable and antibacterial film. Issue 1 (1st March 2015) - Thiel, Karsten; Grunwald, Ingo; Wittig, Linda; Westphal, Nina; Salz, Dirk; Vogel, Konstantin; Ciacchi, Lucio Colombi
Abstract : Bacterial adhesion to the surface of implants in bone tissue may result in serious peri-implant diseases and cannot always be avoided by sterilization prior to implantation. For this reason, different strategies to confer the implant surfaces with intrinsic antibacterial properties are being developed. A major difficulty is that effective antibacterial materials may be detrimental to the adhesion of eukaryotic cells, and be poorly integrated into the host tissue. Here, we develop and characterize a composite coating material comprising silver nanoparticles deeply buried inside a matrix of plasma-polymerized hexamethyldisiloxane. Applied to titanium dental screws, the coating shows a good resistance against stresses from sterilization with β -irradiation and drilling into bone tissue. By varying the parameters of the plasma-depositing process, we are able to either induce or hinder the adhesion of epithelial cells. Through a fluorescence microscopy analysis, we demonstrate that the inclusion of silver nanoparticles in the polymer matrix does not influence the adhesion of fibroblasts and osteoblasts. However, the presence of silver in the coating layer results in dramatically reduced adhesion of Escherichia coli bacteria with respect to uncoated or silver-free coated surfaces.